REPRESENTASI YAHUDI DALAM MEDIA DI INDONESIA - Kukuh Yudha Karnanta (LP3 UMY, 2015)
This poper explores about Jews discourse in media texts in the forms of article after Jews'military aggression to Free Gaza liovement activist in lliay 20, 2010. They are two article hard news published by Jawa Pos in June 31 , 2010 which the titles are Pasca Penyerangan Israel terhadop Kapal lAavi l{iarmora: Ujian Dunia, Ujian AS, and Tentu Saja Israel lAembantah; and a opinion article which the title is Doktrin Dunia tak Berdaya which published in Kompas June 3, 2010. By using critical discourse analysis in the model of social change from Norman Fairclogh and The model ofhistory approach from Ruth Wodak, this paper is orranged by using ethnography methods by observation to Jews ethnic and religion in Surabaya to explore implication of discourse production in socio-cultural context, especially in Surobayo.